石墨烯薄膜、石墨烯超级电容器及其制备方法 (2017)
本发明公开了种石墨烯薄膜、石墨烯超级电容器及其制备方法，用以解决现有技术中的石墨烯制备方法普遍存在着耗时长、能耗高、且不易于大批量制备等缺陷的问题。该石墨烯薄膜的制备方法包括：将氧化石墨烯溶液涂覆在金属基底上；在预设条件下得到干燥固化在所述金属基底上的氧化石墨烯薄膜；对所述氧化石墨烯薄膜进行激光雕刻还原处理，得到石墨烯薄膜；将所述石墨烯薄膜与所述金属基底分离。 The invention discloses a graphene thin film, a graphene super capacitor and a preparation method of the graphene thin film and the graphene super capacitor, and aims at solving the common problems of defects of long time taken, high energy consumption, not easy large-batch preparation and the like of a graphene preparation method in the prior art. The preparation method of the graphene thin film comprises the following steps: coating a metal substrate with a graphene oxide solution; obtaining a graphene oxide thin film dried and cured on the metal substrate under preset conditions; performing laser carving reduction processing on the graphene oxide thin film to obtain the graphene thin film; separating the graphene thin film from the metal substrate.